Penyuluhan Kesehatan Tentang Penyakit Yang Ditimbulkan Oleh Rokok di Desa Haurpanggung Kecamatan Tarogong Kidul Kabupaten Garut - andhika, Andhika Lungguh Perceka; Wahyudin; Iwan Wahyudi; Muhammad Sidiq Nurjaman (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Smoking behavior is a problem related to public health because it can cause various diseases and can even cause death for both smokers and those around them (passive smokers). Everyone already knows that smoking is harmful to health, but in fact smoking behavior is still very difficult to control. find out how much people know about the dangers of smoking. The method applied in this activity is counseling using slides with material related to diseases caused by smoking including the delivery of material about the dangers of smoking, health checks and questions and answers. The results obtained from the counseling were followed by 50 participants from Hauranggung Village including 34 people or 68% are female and 16 people or 32% are male and the level of community awareness of the dangers caused by smoking 86% or 43 residents are aware of the dangers of smoking and 14% or 7 residents do not understand the conclusions obtained from this outreach activity. increase people's knowledge of the dangers of smoking, the impact of smoking for both active and passive smokers and increase public awareness of the dangers of smoking by 86% or as many as 43 people out of 50 participants